Tinjauan Pustaka : MENJELAJAH PERJANJIAN BARU JILID 2 - Silaen, Riste Tioma; Siregar, Oren (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2022)
This book does not spend time speculating on the author of each book and when it was written. Therefore, the reader will have more room to explore the context, intent, and theological message. Readers will be invited to think actively. Readers can carry out further study activities and develop their ideas about the world behind the NT letters. Every detail in each chapter can be used as material for learning and thinking alone and discussion with groups. Therefore, this book is very appropriate for readers who want more in-depth information from the Epistle and Revelation, with some prompts for further study at the end of the discussion of each chapter (Surat). Students and Lecturers of Theology, grades one to three, are urgent to read.